Profile of Patients Referred to a Specialist Oral Medicine and Oral Pathology Unit. - Suraya Hani Mohd Sinon; Nur Syazwani Che Husin; NurulJannah Yusof (Universiti Kebangsaan Malaysia, 2013)
The aim of this study was to determine the profile of patients referred to a specialist oral medicine and oral pathology unit in Kuala Lumpur by reviewing clinical dental records received in Oral Pathology Diagnostic Service (OPDS) in Faculty of Dentistry, UKM from 2001 until 2010.